PEMBELAJARAN MODEL SAVI DALAM MATA PELAJARAN BACA TULIS ALQURAN - Sabariah, Sabariah (LPPM IAIN Parepare, 2018)
This article discusses about the influence of interactive learning media with SAVI model toward the interest in learning BTQ of SMPN 1 Lembang students. This study aims to determine the use of learning with SAVI model, as well as interest in learning BTQ learners in SMPN 1 Lembang, and the influence of learning with SAVI model, on the learning interest BTQ learners in SMPN 1 Lembang. This research type includes quantitative research, location and time of research at SMPN 1 Lembang from July until August 2017. The sample was 30 students by using random sampling technique. Data obtained through observation, questionnaires, and documentation. Then analyzed descriptively and inferensially. Test validity, reliability, regression and correlation test using SPSS version 22 application. The results of this study indicated, (1) Learning media with SAVI model, can be known from the questionnaire, was high category. (2) Learning interest of BTQ learners which is known by the result of questionnaire count was high category. (3) Based on the result of t test, it is concluded that the learning of SAVI model together, have an effect on the interest of BTQ students on PAI learning at SMPN 1 Lembang.